Current Prophylaxis and Treatment Approaches for Acute Graft-Versus-Host Disease in Haematopoietic Stem Cell Transplantation for Children With Acute Lymphoblastic Leukaemia - Wölfl, Matthias; Qayed, Muna; Benitez Carabante, Maria Isabel; Sykora, Tomas; Bonig, Halvard; Lawitschka, Anita; Diaz-de-Heredia, Cristina (Frontiers in Pediatrics, 2022)
Acute graft-versus-host disease (aGvHD) continues to be a leading cause of morbidity and mortality following allogeneic haematopoietic stem cell transplantation. However, higher event-free survival (EFS) was observed in patients with acute lymphoblastic leukaemia (ALL) and grade II aGvHD versus patients with no or grade I GvHD in the randomized, controlled, open-label, international, multicentre Phase III For Omitting Radiation Under Majority age (FORUM) trial. This finding suggests that moderate-severity aGvHD is associated with a graft-versus-leukaemia effect which protects against leukaemia recurrence. In order to optimize the benefits of HSCT for leukaemia patients, reduction of non-relapse mortality – which is predominantly caused by severe GvHD – is of utmost importance. Herein, we review contemporary prophylaxis and treatment options for aGvHD in children with ALL and the key challenges of aGvHD management, focusing on maintaining the graft-versus-leukaemia effect without increasing the severity of GvHD